Technical cooperation under the Colombo Plan report 1950/51-. - Council for Technical Co-operation in Asia and the Pacific (Colombo, Sri Lanka Colombo Plan Bureau, 1950)
Annual
Includes Philippines.
Keywords: Technical assistance -- Asia, Southeastern -- Periodicals; Economic assistance -- Asia, Southeastern -- Periodicals